Association of Preoperative Body Weight and Weight Loss With Risk of Death After Bariatric Surgery - Sun, Yangbo (JAMA Netw Open, 2020)
IMPORTANCE: Perception of weight loss requirements before bariatric surgery varies among patients, physicians, and health insurance payers. Current clinical guidelines do not require preoperative weight loss because of a lack of scientific support regarding its benefits. OBJECTIVE: To examine the association of preoperative body mass index (BMI) and weight loss with 30-day mortality after bariatric surgery. DESIGN, SETTING, AND PARTICIPANTS: This cohort study used data from 480 075 patients who underwent bariatric surgery from 2015 to 2017 in the Metabolic and Bariatric Surgery Accreditation and Quality Improvement Program, which covers more than 90% of all bariatric surgery programs in the United States and Canada. Clinical and demographic data were collected at all participating institutions using a standardized protocol. Data analysis was performed from December 2018 to November 2019. EXPOSURES: Preoperative BMI and weight loss. MAIN OUTCOMES AND MEASURES: 30-day mortality after bariatric surgery. RESULTS: Of the 480 075 patients (mean [SD] age 45.1 [12.0] years; 383 265 [79.8%] women), 511 deaths (0.1%) occurred within 30 days of bariatric surgery. Compared with patients with a preoperative BMI of 35.0 to 39.9, the multivariable-adjusted odds ratios for 30-day mortality for patients with preoperative BMI of 40.0 to 44.9, 45.0 to 49.9, 50.0 to 54.9, and 55.0 and greater were 1.37 (95% CI, 1.02-1.83), 2.19 (95% CI, 1.64-2.92), 2.61 (95% CI, 1.90-3.58), and 5.03 (95% CI, 3.78-6.68), respectively (P for trend < .001). Moreover, compared with no preoperative weight loss, the multivariable-adjusted odds ratios for 30-day mortality for patients with weight loss of more than 0% to less than 5.0%, 5.0% to 9.9%, and 10.0% and greater were 0.76 (95% CI, 0.60-0.96), 0.69 (95% CI, 0.53-0.90), and 0.58 (95% CI, 0.41-0.82), respectively (P for trend = .003). CONCLUSIONS AND RELEVANCE: In this study, even moderate weight loss (ie, >0% to <5%) before bariatric surgery was associated with a lower risk of 30-day mortality. These findings may help inform future updates of clinical guidelines regarding bariatric surgery.